Characterization of the combined effect of high temperature and moisture on methane adsorption in shale gas reservoirs - Zou, Jie; Rezaee, Reza; Xie, Sam; You, L. (ELSEVIER, 2019)
With a significant amount of methane stored in shales in the form of adsorbed gas, it is important to understand the controlling factors of the methane adsorption capacity. Under actual reservoir conditions, the high temperature and moisture are always coexisting which can affect gas adsorption capacity. This paper studied the methane adsorption of shale at different temperatures in dry and wet conditions. The adsorption results indicated that the moisture and high temperature can reduce the adsorbed gas content in shales individually, and the two factors have a synergistic-negative effect on methane adsorption in shales. Thermodynamic parameters showed that the heat of adsorption shows a decreased tendency and the entropy of adsorption becomes less negative after moisturizing the samples. The combined effect of the two factors is sufficiently important in the evaluation of gas adsorption capacity in shale gas systems.